An Animal-Like Cryptochrome Controls the Chlamydomonas Sexual Cycle. Issue 3 (3rd May 2017) - Zou, Yong; Wenzel, Sandra; Müller, Nico; Prager, Katja; Jung, Elke-Martina; Kothe, Erika; Kottke, Tilman; Mittag, Maria
Abstract : The animal-like cryptochrome, which accumulates and is located differentially during the Chlamydomonas life cycle, controls germination in a positive and gametogenesis in a negative manner. Abstract: Cryptochromes are known as flavin-binding blue light receptors in bacteria, fungi, plants, and insects. The animal-like cryptochrome (aCRY) of the green alga Chlamydomonas reinhardtii has extended our view on cryptochromes, because it responds also to other wavelengths of the visible spectrum, including red light. Here, we have investigated if aCRY is involved in the regulation of the sexual life cycle of C. reinhardtii, which is controlled by blue and red light at the steps of gametogenesis along with its restoration and germination. We show that aCRY is differentially expressed not only during the life cycle but also within the cell as part of the soluble and/or membrane-associated protein fraction. Moreover, localization of aCRY within the algal cell body varies between vegetative cells and the different cell types of gametogenesis. aCRY is significantly (early day) or to a small extent (late night) enriched in the nucleus in vegetative cells. In pregametes, gametes and dark-inactivated gametes, aCRY is localized over the cell body. aCRY plays an important role in the sexual life cycle of C. reinhardtii : It controls the germination of the alga, under which the zygote undergoes meiosis, in a positive manner, similar to the regulation by the blue light receptors phototropin and plant cryptochrome (pCRY). However, aCRY acts in combination with pCRY as a negative regulator for mating ability as well as for mating maintenance, opposite to the function of phototropin in these processes.